AGN Feedback Signatures in UV Emission - K. Rubinur (Galaxies, 2024)
Supermassive black holes (SMBH) are believed to influence galaxy evolution through AGN (active galactic nuclei) feedback. Galaxy mergers are key processes of galaxy formation that lead to AGN activity and star formation. The relative contribution of AGN feedback and mergers to star formation is not yet well understood. In radio-loud objects, AGN outflows are dominated by large jets. However, in radio-quiet objects, outflows are more complex and involve jet, wind, and radiation. In this review, we discuss the signatures of AGN feedback through the alignment of radio and UV emissions. Current research on AGN feedback is discussed, along with a few examples of studies such as the galaxy merger system MRK 212, the radio-quiet AGN NGC 2639, and the radio-loud system Centaurus A. Multi-frequency observations of MRK 212 indicate the presence of dual AGN, as well as feedback-induced star-forming UV clumps. The fourth episode of AGN activity was detected in radio observations of the Seyfert galaxy NGC 2639, which also showed a central cavity of 6 kpc radius in CO and UV maps. This indicates that multi-epoch jets of radio-quiet AGN can blow out cold molecular gas, which can further reduce star formation in the center of the galaxies. Recent UV observations of Cen A have revealed two sets of stellar population in the northern star-forming region, which may have two different origins. Recent studies have shown that there is evidence that both positive and negative feedback can be present in galaxies at different scales and times. High-resolution, multi-band observations of large samples of different types of AGN and their host galaxies are important for understanding the two types of AGN feedback and their effect on the host galaxies. Future instruments like INSIST and UVEX will be able to help achieve some of these goals.